HIV-1 Viral Loads Are Not Elevated in Individuals Co-infected With Schistosoma spp. After Adjustment for Duration of HIV-1 Infection - Colombe, Soledad; Corstjens, Paul L. A. M.; de Dood, Claudia J.; Miyaye, Donald; Magawa, Ruth G.; Mngara, Julius; Kalluvya, Samuel E.; van Lieshout, Lisette; van Dam, Govert J.; Downs, Jennifer A. (Frontiers in Immunology, 2018)
Studies of the role of Schistosoma co-infections on plasma HIV-1 RNA (HIV-1 viral load) have yielded incongruent results. The role of duration of HIV-1 infection on the link between Schistosoma and HIV-1 viral load has not been previously investigated. We aimed to assess the impact of HIV-1/Schistosoma co-infections on viral load in Antiretroviral Treatment (ART)-naïve HIV-1 infected people taking into account the duration of HIV-1 infection. We describe 79 HIV-infected outpatients greater than 18 years of age who had never used ART in Mwanza, Tanzania. Schistosomiasis testing was done by urine and stool microscopy and by serum Schistosoma circulating anodic antigen (CAA) testing. Schistosoma positivity was defined as having either test positive. We conducted univariable and multivariable linear regressions to assess the relationship between Schistosoma infection and the log10 of viral load. Duration of HIV infection was calculated using the first measured CD4+ T-cell (CD4) count as a function of normal CD4 count decay per calendar year in drug naïve individuals. An active Schistosoma infection was demonstrated in 46.8% of the patients. The median log10 viral load was 4.5[3.4-4.9] log10 copies/mL in Schistosoma uninfected patients and 4.3[3.7-4.6] log10 copies/mL in Schistosoma infected patients. Schistosoma co-infection was negatively associated with the log10 of viral load after adjustment for Schistosoma intensity as measured by CAA, CD4 counts at time of testing, and duration of HIV-1 infection (β=-0.7[-1.3;-0.1], p=0.022). Schistosoma co-infection was not associated with viral load in univariable analysis. There was also no interaction between Schistosoma positivity and duration of HIV-1 infection. Our study is the first, to our knowledge, to report adjustment for duration of HIV-1 infection when analyzing the relationship between HIV-1 viral load and Schistosoma spp. We found that time infected with HIV-1 has a major effect on the relationship between HIV-1 viral load and Schistosoma infection and may be a critical explanatory factor in the disparate findings of studies on HIV-1 viral load and schistosomiasis. The log10 viral load difference found indicates that Schistosoma co-infection does not make HIV progression worse, and could possibly lead to slower HIV disease progression.